The Development and Validation of Picture Clues as Media for Developing Reading Comprehension Skills Among Grade 5 Learners - Cabalan, Ron Gay Marie P.; Liquido, Ma. Gloria E. (RIRAI Publisher, 2025)
Observations of poor reading comprehension highlight the critical nature of learners at a stage where they are transitioning from “learning to read to reading to learn”. Providing effective strategies, such as utilizing picture clues, is essential to support learners in understanding and analyzing texts independently. While picture clues are commonly used in early childhood education, this study was undertaken to determine the efficacy of picture clues as media for developing reading skills among Grade 5 learners. The descriptive-evaluative research design was employed in this study. This study utilized an intact group which composed of the class to which the picture clues were utilized. The data gathered in this study were treated using arithmetic Mean and percentage and the level of ability of comprehension was determined using the Phil-IRI tool. The Paired Samples t-test was used to determine if there was a significant difference between the pre-assessment and post-assessment scores of the learners. Results revealed that the utilization of picture clues facilitated a significant advancement in the learners' reading comprehension skills. The use of picture clues was found effective in improving learners’ engagement with the text as well as their ability to identify the main idea, make predictions, and draw conclusions. Specifically, the transition from literal skills to critical skills level demonstrated the effectiveness of incorporating visual aids like picture clues in the learning process of the learners. This suggests that utilizing such instructional media can effectively support and foster the development of higher-order thinking abilities, thereby enhancing their overall reading comprehension proficiency.